Net Zero Energy Buildings and the cost per sf - Attallah, Sherif; Shayesteh, Alireza (European Journal of Applied Sciences, 2023)
Zero energy buildings are created and constructed to use the least amount of energy feasible [1]. These structures can produce enough energy to meet or surpass their operating needs when a renewable energy source is added to them [1]. Most modern buildings consume a lot of energy to run the lights, heat the water, chill the air, and power personal electronics [2]. The large energy load will not be greatly mitigated by adding solar systems. However, there are other structures that achieve balance or even tilt the scales in the opposite direction. These are referred to as zero energy structures. The reductions in energy use and carbon footprint must be adjusted to account for real systems, such as the inhabitants and the local climate before renovations may be advised on a continental scale [3]. According to Delavar and Sahebi Energy is an essential resource for the economic growth of today’s businesses [4]. Residential and commercial buildings must utilize a significant amount of energy to provide the services required. The total amount of energy consumed in this industry has been constantly increasing. Due to the large greenhouse gas emissions that arise, effective building management and energy conservation have become top priorities for the energy and environmental sectors all over the world. In this direction, net-zero energy buildings (NZEB) are a very effective way to minimize energy consumption and alleviate environmental impacts in buildings.